ESSM Position Statement "Sexual Wellbeing After Gender Affirming Surgery". Issue 1 (28th December 2021) - Özer, Müjde; Toulabi, Sahaand Poor; Fisher, Alessandra D.; T'Sjoen, Guy; Buncamper, Marlon E.; Monstrey, Stan; Bizic, Marta R.; Djordjevic, Miroslav; Falcone, Marco; Christopher, Nim A.; Simon, Daniel; Capitán, Luis; et al.
Abstract: Introduction: Much has been published on the surgical and functional results following Gender Affirming Surgery ('GAS') in trans individuals. Comprehensive results regarding sexual wellbeing following GAS, however, are generally lacking. Aim: To review the impact of various GAS on sexual wellbeing in treatment seeking trans individuals, and provide a comprehensive list of clinical recommendations regarding the various surgical options of GAS on behalf of the European Society for Sexual Medicine. Methods: The Medline, Cochrane Library and Embase databases were reviewed on the results of sexual wellbeing after GAS. Main Outcomes Measure: The task force established consensus statements regarding the somatic and general requirements before GAS and of GAS: orchiectomy-only, vaginoplasty, breast augmentation, vocal feminization surgery, facial feminization surgery, mastectomy, removal of the female sexual organs, metaidoioplasty, and phalloplasty. Outcomes pertaining to sexual wellbeing- sexual satisfaction, sexual relationship, sexual response, sexual activity, enacted sexual script, sexuality, sexual function, genital function, quality of sex life and sexual pleasure- are provided for each statement separately. Results: The present position paper provides clinicians with statements and recommendations for clinical practice, regarding GAS and their effects on sexual wellbeing in trans individuals. These data, are limited and may not be sufficient to make evidence-based recommendations for every surgical option. Findings regarding sexual wellbeing following GAS were mainly positive. There was no data on sexual wellbeing following orchiectomy-only, vocal feminization surgery, facial feminization surgery or the removal of the female sexual organs. The choice for GAS is dependent on patient preference, anatomy and health status, and the surgeon's skills. Trans individuals may benefit from studies focusing exclusively on the effects of GAS on sexual wellbeing. Conclusion: The available evidence suggests positive results regarding sexual wellbeing following GAS. We advise more studies that underline the evidence regarding sexual wellbeing following GAS. This position statement may aid both clinicians and patients in decision-making process regarding the choice for GAS.